Evgeny Vodolazkin’s Laurus: a dialogue with the Old Russian literary tradition - Trojanowska, Beata (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2018)
The paper is an attempt at describing similarities and differences between Evgeny Vodolazkin’s novel Laurus (Lavr) and the Old Russian literature, in particular such genres of the latter as the lives of saints, religious travel writing, chronicle and paleia. The analogy with ancient Greek novel is also mentioned. The author of the paper on the one hand stresses that due to its syncretic character, the novel Laurus absorbs selected elements of the above-mentioned texts of the past, and on the other hand analyses Vodolazkin’s innovative treatment of time. This last aspect contributes to the text’s originality and makes it possible for the writer to connect situations and personages from the past with the present and the future, which, altogether, renders Laurus universal.